Análise temporal de criminalidade e relação com doenças cardiovasculares no município de São Paulo, 2010-2020 - Rodella, Eliazer (2023)
Introduction: The city of São Paulo, due to its size, grandeur and financial, attracts criminals who make their victims, between 2010 and 2020 several crimes occurred, we highlight those that will be the subject of research in this work, which are robbery , theft and theft of common things that reach more than 4.3 million victims. On the other hand, cardiovascular problems are also of enormous relevance. A study by the Brazilian Society of Cardiologists shows that in Brazil, on average, 1,100 people lose their lives due to heart problems, that is, every 90 (ninety) seconds a person dies due to cardiovascular problems in Brazil.Objective: To study the temporal distribution of robbery, theft and theft of common things and indicators related to deaths resulting from cardiovascular diseases and analyze the relationships between them in the city of São Paulo, from 2010 to 2020. Methods: This is a ecological, descriptive and exploratory study, with an analytical component, in which crime data were collected at the Public Security Secretariat of the State of São Paulo, as well as indicators of deaths due to cardiovascular diseases, registered, respectively, in the Hospital Admission System and the Information on Mortality, available on TabNet (public domain generic tabulator that allows you to quickly organize data according to the query you want to tabulate) from the São Paulo Municipal Health Department. The indicators were described temporally and related, in the period between 2010 and 2020, in order to characterize their trends over time and verify the existence of patterns. Results: after processing data on robbery, theft and theft of common things in a temporal, descriptive, exploratory analysis with an analytical component in the city of São Paulo, to verify whether or not it contributed to the occurrence of heart problems that lead to death between 2010 to 2020, we can conclude that, considering the correlation index achieved with Spearman's Non-Parametric Test, there is a moderate correlation, closer to a strong correlation, of 0.63, since, if the p-value is less than 0 .05%, we have enough input to accept the Alternative Hypothesis (H1), that is, that crime in the city of São Paulo may be one of the determining factors related to the incidence of cardiovascular problems, which is in line with Weisbug's research, (2019) from George Mason University Criminol law & Soc, USA, published in the Journal of Contemporary Criminal Justice that indicates a link between crime and health.